Utilization of Liquid Palm Organic Fertilizers and M-Bio Biological Fertilizers Against Growth and Production in Okra Plants (Abelmoschusesculentus L. Moench) - Heru Kurniawan; Asmah Indrawati; Gusmeizal Gusmeizal (Jurnal Ilmiah Pertanian ( JIPERTA), 2019)
Okra plant is becoming to be one of favortite vegetable in Indonesia since then the deman of this plant is growing very rapidly. The aim of this research is to Utilize Palm Oil Liquid Organic Fertilizer and M-Bio Biofertilizer Against Growth and Production in Okra Plants (Abelmoschusesculentus  L.  Moench).  This  study  used  a  Randomized  Block  Design (RBD) with 2 replications. Factorial consisting of II treatment factors, Factor I treatment given P0: Without Liquid Palm Oil Organic Fertilizer, P1: Provision of PKS liquid fertilizer and Factor II, treatment of giving M-Bio. Parameters observed in this study were  vegetative dan generative. The results showed that the treatment of oil palm liquid organic fertilizer had no significant effect on vegetative and generative observed parameters. The treatment of M-Bio biofertilizer significantly affected the vegetative and generative observation parameters where the best dose was treatment  6%. The treatment of the combination of liquid organic fertilizer from palm oil waste and M-Bio biological fertilizer has no significant effect on all parameters of vegetative and generative observations.